2013
DOI: 10.4049/jimmunol.1202950
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial–Mesenchymal Transition Induces an Antitumor Immune Response Mediated by NKG2D Receptor

Abstract: Epithelial–mesenchymal transition (EMT) is a morphogenetic process characterized by the acquisition of mesenchymal properties linked with an invasive phenotype and metastasis of tumor cells. NK group 2, member D (NKG2D) is an NK cell–activating receptor crucially involved in cancer immunosurveillance. In this study, we show that induction of EMT by TGF-β stimulation of human keratinocytes, by glycogen synthase kinase-3β inhibition in several epithelial tumor cell lines, and by Snail1 overexpression in colorect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 42 publications
3
69
1
Order By: Relevance
“…Strongly supporting the above notion, our studies show that in addition to promoting an invasive phenotype (18,19,44), EMT renders cancer cells more susceptible to NK-mediated killing, in vitro, by modulating activating and inhibitory ligands. This is consistent with a singular in vitro study that showed increased susceptibility of a colon cancer cell line to NK cells (45). More importantly, for the first time to our knowledge, we have demonstrated the effect of this enhanced susceptibility on tumor metastasis in vivo in multiple mouse models.…”
Section: Discussionsupporting
confidence: 76%
“…Strongly supporting the above notion, our studies show that in addition to promoting an invasive phenotype (18,19,44), EMT renders cancer cells more susceptible to NK-mediated killing, in vitro, by modulating activating and inhibitory ligands. This is consistent with a singular in vitro study that showed increased susceptibility of a colon cancer cell line to NK cells (45). More importantly, for the first time to our knowledge, we have demonstrated the effect of this enhanced susceptibility on tumor metastasis in vivo in multiple mouse models.…”
Section: Discussionsupporting
confidence: 76%
“…Epithelial-mesenchymal transitions (EMT) induced the expression of NKG2DLs, rendering EMT tumor cells more susceptible to elimination by NK cells [36], thus supporting our observations of high MICA/B expression by the invasive cell line MDA-MB-231. U-937 monocytic cell lines have high surface expression as well as secrete MICA and MICB.…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, co-culture with hyperploid cancer cells induced the expression of NKG2D and DNAM-1 on NK cells, and experiments performed using blocking antibodies highlighted the relevance of these receptors in the cytotoxic response of NK cells against polyploid cancer cells. Altogether, we describe herein that, additionally to oncogenes, proliferative, tumor progression and stress signals, which are known to regulate NKG2D ligands expression in cancer, [26][27][28][29][30] the induction of hyperploidy is involved in the activation of the NKG2D-mediated cancer immunosurveillance.…”
Section: Discussionmentioning
confidence: 92%
“…22 Among NK cell receptors, NKG2D plays a key role in the immune response against cancer. 18,23 Genotoxic stress, 24 Sp1 transcription factors, 25 proliferative and tumor suppressor signaling pathways, 26,27 and tumor progression 28,29 are known to induce the expression of NKG2D ligands in cancer cells, initiating an antitumor immune response. [30][31][32] Activated NK cells are capable of killing a broad range of cancers and of regulating the innate and adaptive immune responses through the secretion of cytokines, such as IFN-g.…”
Section: Introductionmentioning
confidence: 99%